2019
DOI: 10.1002/smll.201900011
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Design of Hollow Flower‐Like g‐C3N4@PDA Organic Framework Nanospheres for Realizing an Efficient Photoreactivity

Abstract: Organic framework polymers have attracted much interest due to the enormous potential design space offered by the atomically precise spatial assembly of organic molecular building blocks. The morphology control of organic frameworks is a complex issue that hinders the development of organic frameworks for practical applications. Biomimetic self‐assembly is a promising approach for designing and fabricating multiple‐functional nanoarchitectures. A bioinspired hollow flower‐like organic framework nanosphere hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…Therefore, the OCN-3 catalyst had a peak external QE of 26.96% at 400 nm and 4.28% at 420 nm (Fig. 3 e), which outperformed in the g-C 3 N 4 -based catalysts reported in the literature (Table S4), including NiMo/g-C 3 N 4 , PDA@g-C 3 N 4 , Ni(OH) 2 /CdS/g-C 3 N 4 [ 9 , 13 , 29 , 39 , 46 ]. The stability of the OCN-3 was tested by cyclic photocatalytic H 2 evolution experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the OCN-3 catalyst had a peak external QE of 26.96% at 400 nm and 4.28% at 420 nm (Fig. 3 e), which outperformed in the g-C 3 N 4 -based catalysts reported in the literature (Table S4), including NiMo/g-C 3 N 4 , PDA@g-C 3 N 4 , Ni(OH) 2 /CdS/g-C 3 N 4 [ 9 , 13 , 29 , 39 , 46 ]. The stability of the OCN-3 was tested by cyclic photocatalytic H 2 evolution experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Researches have shown that heteroatom such as nitrogen (N), oxygen (O), sulfur (S), phosphorus (P) dopants play a vital role in promoting the photocatalytic activity of g-C 3 N 4 through broader light-responsive range, higher light utilization efficiency owing to the reduced band gap [13,14]. For instance, Li et al [15] found that P-doping could significantly improve the electronic conductivity of g-C 3 N 4 , leading to the inhibition of recovering of photoseparated charges and holes under visible-light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, copious effort s have been devoted to the reconstruction of graphitic carbon nitride (g-C 3 N 4 ) due to its fascinating physicochemical, optical, and electronic properties [6,7] . To address the intrinsic drawbacks of bulk g-C 3 N 4 , the fast recombination of photogenerated electron-hole pairs and inefficient interfacial charge transfer, a variety of hollow morpholo-gies have been designed to achieve 3D micro-/nanospheres [8,9] , 2D/3D flower-like nanospheres [10,11] , 1D nanofibers [12] , 1D/2D nanotubes [13] , horn-like microtubes [14] , etc. Among the hollow structures of g-C 3 N 4 , the low dimensionnal morphologies, especially 1D tubes, have been proven to benefit the oriented electron transfer from matrix to surface and then the transmission along longitudinal direction, which become a hot topic in the g-C 3 N 4based photocatalysis field [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…[269] By means of electrostatic interaction, PDA was decorated with graphitic carbon nitride nanosheets, giving rise to a photocatalytic system with enhanced performance. [270]…”
Section: Immobilization Of Organic Speciesmentioning
confidence: 99%